Tax Reform in an Era of Budget Stress, Inequality, and International Mobility - Alan J. Auerbach (Swiss Journal of Economics and Statistics, 2017)
This paper is based on my Walter Adolf Jöhr Lecture given at the University of St Gallen on May 20, 2016, as part of the annual CEPR Public Economics Symposium 2016 in St. Gallen, organized by Henrik Kleven and Christian Keuschnigg.
Keywords: 330